Enhancing Village Image through Murals In the Astagina Field, Padangsambian Kelod Village, Denpasar - Made Arini Hanindharputri (Visual Communication Design Department of Universitas Pelita Harapan, 2021)
The Covid-19 pandemic that has hit all countries in the world including Indonesia, has made access to tourism and community activities not optimal. However, in a situation like this, the city of Denpasar, Bali, which has been named a creative city with a cultural perspective by the Indonesian Creative Agency, continues to carry out branding activities in the hope that after the pandemic ends, both local and foreign people will continue to visit Bali and carry out their usual activities. One tourist village that wants to do branding is Padang Sambian Kelod Village. This village collaborates with the Bali Design and Business Institute to carry out the Community Service program in the form of a mural which is carried out in Astagina Field, as a form of enhancing the image of the village and welcoming the planned Porsenides (Village Sports and Art Week) activities when the pandemic situation has decreased or ended. The method used is a participatory design approach, which will connect humans (lecturers and students who carry out the mural), place (the identity of the tourist village) and function functions (knowledge and action). The result of this activity is the design of a mural that features Balinese traditional sports as a characteristic of Padangsambian Kelod Village, where this mural is expected not only to beautify the village, but also to improve the image of the village itself, and of course to become an icon of Porsenides in the village.